The role of microvesicles in cancer progression and drug resistance. (29th January 2013) - Jorfi, Samireh; Inal, Jameel M.
Abstract : Microvesicles are shed constitutively, or upon activation, from both normal and malignant cells. The process is dependent on an increase in cytosolic Ca 2+, which activates different enzymes, resulting in depolymerization of the actin cytoskeleton and release of the vesicles. Drug resistance can be defined as the ability of cancer cells to survive exposure to a wide range of anti-cancer drugs, and anti-tumour chemotherapeutic treatments are often impaired by innate or acquired MDR (multidrug resistance). Microvesicles released upon chemotherapeutic agents prevent the drugs from reaching their targets and also mediate intercellular transport of MDR proteins.